Second Millennium B.C. Cypriot and Cretan Onomastica Reconsidered - Astour, Michael С.
I. Cyprus (Alašia): A. Evidence from Alalah (17th and 15th centuries); B. Evidence from Tell el-Amarna (14th century); C. Evidence from Ugarit (14th-13th centuries); D. Evidence from Egypt (Early 11th century). Conclusion. II. Keftiu (Crete). Conclusion.